Zircon U–Pb and Lu–Hf isotopic systems in ediacaran to Fortunian "Taourirt" granitic ring complexes (Silet and In Tedeini terranes, Tuareg shield, Algeria). (August 2020) - Azzouni-Sekkal, Abla; Bonin, Bernard; Bowden, Peter; Bechiri-Benmerzoug, Faten; Meddi, Yassamina
Abstract: The Tuareg shield in North-West Africa is composed of an assembly of Neoproterozoic continental and oceanic terranes, as well as Archean and Paleoproterozoic terranes separated by major continental shear zones. In the Silet terrane, the igneous suite of Silet-Taourirts is composed of post-collisional ring-complexes of ferroan alkaline and alkali-calcic granites. Six ring-complexes have been dated using the U–Pb SHRIMP technique on zircon. The alkaline Tin Erit (584.8 ± 2.0 Ma), Tihoiiarene (569.8 ± 4.8 Ma) and Tioueine (561 ± 6 Ma) complexes are older than the alkali-calcic Issedienne (538.7 ± 2.9 Ma), Tesnou (536.5 ± 6.7 Ma) and Ait Oklan (529.3 ± 3.1 Ma) complexes. Sharing an enriched mantle source, the complexes display a secular variation of crustal contamination marked by decreasing εHf(t). The oldest alkaline complexes are related to the tectonic escape of the Tuareg terranes to the north after the climax of Pan-African orogeny, while the youngest alkali-calcic complexes were emplaced after the 575-555 Ma intra-continental Murzukian event. Highlights: Taourirt granitic ring complexes postdate Pan-African orogenic episodes by more than 50 My. Zircon U–Pb SHRIMP isotopic data evidence two periods of igneous emplacement: 585-560 Ma and 560-525 Ma. Lu–Hf isotopic data suggest secular variations with increasing contamination by old LATEA basement. Throughout the Hoggar, three discrete episodes were identified from west to east.